ASSESSMENT OF THE KANSAS FOODBORNE ILLNESS COMPLAINT SYSTEM AND THE RESTAURANTS ASSOCIATED, 2009-2014 - Stein, Zachary (My University, 2015)
The state agencies of Kansas utilize many different channels of disease reporting and disease detection. Foodborne illness oftentimes goes undetected and a foodborne illness complaint system is a method that puts the ill persons directly in contact with health administration professionals. Complaint systems can decrease the barriers between disease reporting and epidemiologists and can be more rapidly assessed than other methods of surveillance. Analysis of these complaints provides policymakers and health professionals with more complete data on which to base decisions and actions. The goal of this field experience and capstone project with the Kansas Department of Health and Environment (the KDHE) was to analyze the Kansas Department of Agriculture’s foodborne illness complaint system, utilizing data from Kansas Food Establishment (KFE) complaints, and the KDHE’s foodborne outbreak investigation data for the period 2009 to 2014. All data was cleaned and compiled into singular files and assessed with SAS and Excel. Count data were assessed and KFE variables were analyzed for contributing factors in complaint submissions. KFE variables (Risk Assessment Code, Principal Food Type, and Franchise Status) all served as contributors to the probability that a KFE will be investigated, but there were no significant contributions to the probability of an outbreak investigation. Complaint variables (Anonymity and Complaint Submission Method) were assessed for an association with a complaint being investigated with anonymity being a significant contributor. Complaint submission method was then found to be a significant contributor to the probability of a complainant submitting a complaint anonymously. Steps taken to increase telephone complaints and non-anonymous complaints could potentially increase the number of detected outbreaks in Kansas and give health professionals a better picture of the impact of foodborne illness on Kansas.
Keywords: Foodborne Illness; Kansas; Complaint; KDHE; KDA; Public Health (0573)